Jerusalén en el judaísmo - Jospe, Raphael (Revista de Estudios Árabes, 2014)
In judaism, religion and state are the components that form the nation. The author remarks the importance of Jerusalem to Judaism, citing Biblical references, the Torah and Talmud. He considers that the Jews were forced in exile from the city for over nineteen centuries, but always felt the need to return. Jerusalem has universal spiritual significance for the three major monotheistic religions, but particular significance to Jews. But, historical and national dimensions makes jerusalem's character primarily jewish.